Sistem Pemerintahan Islam: Studi Pemikiran Politik Muhammad Imarah - Ihsannudin, Nurul; Nisa`, Khoirun (Proceedings of Annual Conference for Muslim Scholars, 2019)
Political and Islamic discussions have taken place from the early days of Islam. Some muslims think that Islam carries political teachings, while some deny it. This short article attempts to examine the political thoughts of Muhammad Imarah, a muslim thinker from Egypt. This study tries to answer; How does Muhammad Imarah think about the Islamic government system? What does he think about the Khilafah? What is the main principle of the government system according to him? The three questions are answered through descriptive-analytic method, with the result that the government system according to Imarah is the creation of human (ijtihad). So that the khilafah in the prophetic period and khulafa rāshidûn is also the result of ijtihad, not revelation from God. And the main principle of a government system, according to Imarah, is deliberation (al-shûrâ).